Analisis Efektifitas Program Keluarga Harapan (PKH) Dalam Mengentaskan Kemiskinan Di Kabupaten Poso Tahun 2010 – 2018 - Shanni Feria Juliana; Abdi Sakti Walenta; Yulian Rinawaty Taaha; Silva Anita Pesak (Fakultas Ekonomi Universitas Kristen Tentena, 2023)
This study aims to analyze the effectiveness of the Family Hope Program (PKH) in poverty alleviation in Poso Regency. The research was conducted in Poso Regency, Central Sulawesi Province. The selection of the research site is carried out by Purposive sampling, which is direct selection with several considerations because the location is considered to have criteria that are in accordance with the purpose of the study. Population is all data from 2007 from the Family Hope Program to 2018. While the sample referred to is Poverty Rate Realization Data for 2010 - 2018 sourced from the Central Bureau of Statistics of Poso Regency, Data on the Target of Poverty Reduction in 2010 - 2018 sourced from the Regional Planning and Development Agency of Poso Regency. The results of the research of the Family Hope Program in alleviating poverty in Poso district are classified as Effective Criteria as a program that reduces poverty. It is evident from the average presentation of the Effectiveness Criteria which reached 98.78% of the effectiveness rate of the Family Hope Program. So the program can be concluded that the objectives of this program as a poverty alleviation program in the regions can be achieved and implemented properly and correctly. This program is a medium and long-term goal program whose benefits can be felt in five to ten years and it is proven that in 2018 this program has been going on for approximately 10 years can be felt in 2018 where the poverty rate is getting lower even though the number of people is increasing.